Analisis Pengaruh Adopsi E-Commerce Terhadap Kinerja Umkm di Young Enterpreneur Bojonegoro - Wahyu Saputri; Badiatud Durroh; Fina Sulistiya Ningsih (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the influence of technology, organization, and inclusiveness variables on e-commerce adoption and MSME performance in the Young Entrepreneur Bojonegoro (YEB) community. This study uses a quantitative and explanatory approach. The sample consisted of 124 YEB MSME respondents selected using the Slovin formula and purposive sampling technique. The data obtained were analyzed using WarpPLS software through outer model testing, inner model testing, and hypothesis testing. The variables of technology, organization, and inclusiveness had a positive and significant effect on the adoption of e-commerce. Furthermore, the adoption of e-commerce also had a significant positive effect on MSME performance. The technology factor also had a direct positive impact on MSME performance. However, organizational and inclusiveness factors do not have a direct effect on MSME performance, emphasizing the important role of e-commerce adoption as a mediating variable. These findings provide guidance for local governments and entrepreneurial networks to strengthen technological infrastructure and provide digital skills training for MSME actors. Increased e-commerce adoption driven by these factors will contribute to improved operational efficiency, market expansion, and the competitiveness of MSMEs, which in turn will support the growth of Indonesia's economy, which is dominated by the MSME sector.